2014
DOI: 10.1159/000366364
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Promotes ROS Detoxification Against Hypoxia/reoxygenation-Induced Oxidative Stress Through FoxO3a/PGC-1a Dependent Superoxide Dismutase

Abstract: Background/Aims: Acetylcholine (ACh) is known to modulate the cardiac redox environment and thereby suppress reactive oxygen species (ROS) generation during oxidative stress. However, there is little information about its regulation on ROS clearance. Here we investigate the beneficial effects of ACh on superoxide dismutase (SOD) as key ROS-detoxifying enzyme system in cultured rat cardiomyoblasts. Methods: H9c2 cells were subjected to hypoxia/reoxygenation (H/R) to mimic oxidative stress. Western blot was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…45 Previous studies in our lab have shown that ACh benefits to the heart and endothelium by acting on M AChR. [14][15][16]46 M3 AChR siRNA as well as 4-DAMP, significantly abolished the protective effect elicited by ACh, suggesting that the action of ACh on ER stress was mediated mainly by M3 AChR. Intriguingly, our results also showed that M3 AChR siRNA abolished ACh-elicited restoration of AMPK during H/R.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…45 Previous studies in our lab have shown that ACh benefits to the heart and endothelium by acting on M AChR. [14][15][16]46 M3 AChR siRNA as well as 4-DAMP, significantly abolished the protective effect elicited by ACh, suggesting that the action of ACh on ER stress was mediated mainly by M3 AChR. Intriguingly, our results also showed that M3 AChR siRNA abolished ACh-elicited restoration of AMPK during H/R.…”
Section: Discussionsupporting
confidence: 76%
“…The endothelial cells were subjected to hypoxia for 8 h to induce simulated ischemia as previously described. 46 For reoxygenation, the medium was replaced with fresh serum-free F12K medium and rapidly transferred into a normoxic incubator (5% CO 2 and 95% air) for 16 h. Then the cells were divided randomly into the following groups for treatment: (1) Con: culture normally with F12K; (2) ACh: administration of ACh (10 ¡6 M) alone; (3) H/R: 8 h of hypoxia followed by reoxygenation for 16 h; (4) H/R C 4-PBA: 4-PBA (10 ¡4 M) was added at the onset of reoxygenation; (5) H/R C 4-DAMP C ACh: M3 AChR inhibitor 4-DAMP (10 ¡6 M) was used in combination with ACh (10 ¡6 M) at the onset of reoxygenation. These agents were all purchased from Sigma.…”
Section: Cell Treatmentmentioning
confidence: 99%
“…Our study showed that resistin can inhibit lipid β oxidation and explored a potential mechanism by which resistin regulates lipid metabolism. The increase of PGC-1α activity has been considered as a valid therapeutic target in the amelioration of several metabolic diseases [17]. Moreover, in vivo studies have shown that specific overexpression of PGC-1α in skeletal muscle tissue provides strong beneficial effects and protects against age-associated diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…Both these aforementioned processes are tightly regulated by a set of nuclear receptors called peroxisome proliferator-activated receptors (PPARs) [9,10]. PPARγ coactivator 1-α (PGC-1α) is one of the best characterized regulatory proteins, and it interacts with numerous nuclear receptors (including PPARs) and regulates various aspects of cellular energy metabolism, mainly via the regulation of mitochondria number and functions [11,12,13,14]. Interestingly, recent data imply that PGC-1α is also involved in the uptake, storage and turnover of glucose and FFAs [15,16].…”
Section: Introductionmentioning
confidence: 99%